Domestic violence as a threat to maternal and child well-being in an urban migrant community in Peru - Brieanne K. Kohrt; Sandra Barrueco; Catalina P. Pérez
OBJECTIVE: To examine the impact that domestic violence (DV) has on hindering the success of urban migrants in Peru and any association with maternal depression, impaired parenting, social capital, and child development. METHODS: This was a cross-sectional study consisting of structured interviews with 97 mothers and their school-aged children in El Porvenir, a predominantly migrant area of the city of Trujillo, Peru. Data collection occurred in February-June 2011. Proven tools previously validated for use in Spanish were used to assess the following variables: maternal depression, social capital, domestic violence, parenting behaviors, child socioemotional development, and child cognitive development. Correlational, multiple regression, tests of interaction, and indirect/mediator models were used for analysis. RESULTS: Sixty-five percent of women reported currently experiencing DV. DV strongly predicted depression (P < 0.001). Women who reported DV were less likely to be employed (P < 0.05), had lower cognitive social capital (P < 0.01), engaged in fewer caregiving activities (P < 0.05), had less maternal energy (P < 0.05), and were less warm (P < 0.05). DV was associated with internalizing behaviors in children (P < 0.01), with impaired parenting partially mediating this relationship. CONCLUSIONS: DV compromises women's mental health and parenting ability. High rates of DV among urban migrants affect the whole community by hindering employment potential and reducing trust among community members. Interventions targeting DV-related variables (e.g., substance abuse and limited job opportunities for men) could reduce the deleterious effects of DV on urban migrant communities across Latin America.